2011
DOI: 10.1002/tox.20730
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PP2A and the consequent activation of JNK/c‐Jun are involved in tributyltin‐induced apoptosis in human amnionic cells

Abstract: Tributyltin (TBT), a highly toxic environmental contaminant, has been shown to induce mitochondrial-dependent apoptosis in several mammalian cells. However, the upstream signal transduction pathways involved in TBT-induced apoptosis are still not fully elucidated. In this study, the protein phosphatase (PP) 2A, microtubule organization, and mitogen-activated protein kinases (MAPKs), including JNK, p38 and their downstream transcription factors, c-Jun and ATF-2, respectively, were investigated in human amnionic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…However, unlike the previous studies, P38 was not activated. Actually, in Zhang's study (Zhang et al, ), although JNK and P38 were activated in response to TBT, surprisingly, while JNK inhibitors were able to induce a response to significantly reduce caspase‐3 activation, P38 inhibitors were not, suggesting that P38 does not seem to play a pivotal role in regulating cell death. In the current study, inhibition of ERK and JNK not only largely diminished the TBT‐induced hyperphosphorylation of VASP but also recovered the cellular morphology and rescued cells from death.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…However, unlike the previous studies, P38 was not activated. Actually, in Zhang's study (Zhang et al, ), although JNK and P38 were activated in response to TBT, surprisingly, while JNK inhibitors were able to induce a response to significantly reduce caspase‐3 activation, P38 inhibitors were not, suggesting that P38 does not seem to play a pivotal role in regulating cell death. In the current study, inhibition of ERK and JNK not only largely diminished the TBT‐induced hyperphosphorylation of VASP but also recovered the cellular morphology and rescued cells from death.…”
Section: Discussionmentioning
confidence: 94%
“…A wealth of studies have confirmed that TBT causes disruption of actin filaments (Cima and Ballarin, 2000;Tsukazaki et al, 2004;Zhu et al, 2007;Zhang et al, 2013), which may be the key factor that triggers apoptosis (Cabado et al, 2004). Changes in cell morphology are associated with reorganization of actin filaments, mostly depending on their intrinsic ability to rapidly assemble and disassemble, indicating a key role of the actin cytoskeleton in the complex network that engages membrane-related events and signal transduction cascades (Cabado et al, 2004;Ferreira et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These reports suggested that upstream players of both JNK and ERK might be involved in this process. Therefore, since PP2A can dephosphorylate both JNK and ERK, leading to inactivation of JNK and ERK and, directly, to dephosphorylation of K8 pSer431, we examined the effects of cerulein on PP2A expression (Tao et al, ; Levallet et al, ; Zhang et al, ). As expected, cerulein reduced the expression of PP2A [Fig.…”
Section: Discussionmentioning
confidence: 99%